Badania metaloznawcze poznańskiego miecza św. Piotra z Muzeum Archidiecezjalnego w Poznaniu - Nosek, Elżbieta M.; Stępiński, Janusz (Ecclesia. Studia z Dziejów Wielkopolski, 2011)
The authors present the results of a metallurgical study of the Poznań sword of St. Peter conducted in 2009. Analysis of the chemical composition of the metal of the blade helped to determine the technology used in its manufacture and consequently made it possible to specify the age and origin of the sword. The authors made an attempt to describe the sword of St. Peter and assign it to an adequate type of one blade weapons. In determining the presumed age of the sword a list of objects that resemble it visually (two 13th century cleavers) or are decorated with evidently related images (Greek vases) proved helpful.